Studies of bioactivity of proteins encapsulated in liposomes - Ho, Amelia May Teng. (2013)
One of the leading causes for blindness in the developed world is Age-related macular degeneration (AMD). The eye has a unique structure with barriers which pose challenges for drug delivery, especially to the posterior segment of the eye. As such, drug delivery systems such as liposomes have recently been investigated.